Sikap Toleransi Beragama pada Siswa Sekolah Menengah Atas: Pengaruh Kontrol Diri dan Lingkungan Pendidikan - Ramdhani, Abdurrahman Ali; Andhita Dessy Wulansari; Guntur, Ahmad Jauhari (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
In Indonesia, efforts to prevent inter-religious conflict must be encouraged. Instilling Religious Tolerance Attitudes among students will make the next generation of the nation accustomed to respecting differences so that they can maintain harmony in a pluralistic society. This study aims to determine (1) the influence of Self-Control and Educational Environment factors on Religious Tolerance Attitudes and (2) the regression model of Religious Tolerance Attitudes based on the factors of Self-Control and Educational Environment. This study uses a quantitative approach with a linear regression analysis technique. Data were obtained from a sample of 189 high school students. The results of the study showed: (1) Self-Control and Educational Environment have a significant effect on the Religious Tolerance Attitudes with R2 of 44.9%; and (2) The regression model is, Y = 42.010 + 0.310X1 + 0.251X2, meaning that Self-Control and Educational Environment have a positive effect on increasing the Religious Tolerance Attitudes.